What are coastal cities doing about the problem of marine litter? A case study in southern Brazil - de Ramos, Bruna; Kitzmann, Dione Silveira (Desenvolvimento e Meio Ambiente, 2022)
Beach management is a key issue in combating marine litter, especially in tourist areas. It is necessary to promote government initiatives that refine local autonomy to improve the quality of beaches. Partnerships between interested institutions at the local level are stimulated to fight against environmental, economic, and social problems. Marine litter, as a more holistic problem, is growing in the international and national sphere, support programs are being developed, with possible advantages at the local level. Cassino Beach in Rio Grande, Brazil, was used as a case study to evaluate the current approaches to managing marine litter, with a focus on tourism-generated litter, analyzing the weaknesses and strengths of municipal management. The case presented as weaknesses a lack of awareness and policy, administrative deficiencies, few resources, and few spaces that promote public participation. Knowledge and information, institutional competencies, partnership, and strategies appeared as strong points. It was possible to observe that the municipality of Rio Grande is assimilating problems, planning actions and few projects are being implemented.